Effect of Irrigation by Waste Water on Accumulation of Heavy Metals in Soil and Plant. - Hassan, Khalida A. K.; Mosa, Rezan I.; Rajab, Shayma M. (Science Journal of University of Zakho, 2015)
A pot experiment was carried out to determine the effect of using waste water irrigation on the concentrations of (Pb, Cd, Cu and Zn) in soil and their subsequent accumulation in plant. Waste water was diluted to give four treatments: T1 (waste water), T2 (1:1), T3 (2:1) well water: waste water and T4 (well water) as control. Higher concentrations of Pb, Cd, Cu and Zn were observed in soil of T1 compared toT4. Pb and Cd in (tops and roots) of chard were above the maximum permissible level in vegetables (WHO,1984). The results also showed a decrease in microbial density caused by high level of heavy metals concentration and an increase in aggregate stability.